2009
DOI: 10.1111/j.1365-4632.2009.03771.x
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival in erythrodermic cutaneous T‐cell lymphoma: an analysis of prognostic factors in a cohort of patients with erythrodermic cutaneous T‐cell lymphoma

Abstract: Serum LDH and age were the strongest predictive factors for OS in E-CTCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 46 publications
3
62
1
2
Order By: Relevance
“…124 It appears that the overall prognosis of SS/erythrodermic MF (E-CTCL) is improving; and in a recent report of 124 patients with E-CTCL, there was a median OS of 5.1 years (range, 0.4-18.6 years). 125 When patients were stratified according to Sézary cell (SC) counts, the median OS was 7.6 years for patients with less than 1000 SC/L versus 2.4 years for those with more than 10 000 SC/L. In multivariate analysis, advanced age and elevated lactate dehydrogenase were the strongest predictors of a poor prognosis.…”
Section: Sé Zary Syndromementioning
confidence: 99%
“…124 It appears that the overall prognosis of SS/erythrodermic MF (E-CTCL) is improving; and in a recent report of 124 patients with E-CTCL, there was a median OS of 5.1 years (range, 0.4-18.6 years). 125 When patients were stratified according to Sézary cell (SC) counts, the median OS was 7.6 years for patients with less than 1000 SC/L versus 2.4 years for those with more than 10 000 SC/L. In multivariate analysis, advanced age and elevated lactate dehydrogenase were the strongest predictors of a poor prognosis.…”
Section: Sé Zary Syndromementioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] However, none of these markers is directly associated with the tumor phenotype of the SS cells and they seem to be mere markers of risk or, at best, the result of some deregulated mechanisms. Here we describe, for the first time, the prognostic significance of two antigens directly related to T-cell function, and thus possibly involved in the pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,11,12 Previous studies of prognostic indicators in SS showed that circulating Sézary cell count, high CD4/CD8 ratio, advanced age, high lactate dehydrogenase serum level and a high white blood cell count were associated with an unfavorable outcome. [13][14][15][16][17][18][19][20] Up to now, scanty data have been provided concerning possible associations between the immunophenotype of circulating CD4 + T cells and survival in SS. As for other hematologic malignancies, 21,22 it is important to clarify the prognostic relevance of activation of homing receptors expressed by circulating CD4 + T cells in SS, since these markers might be directly linked to the pathogenesis and outcome of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the median overall survival in patients with erythrodermic CTCL is 5.1 years, with the strongest predictive factors being elevated serum lactate dehydrogenase, advanced age, and the absolute Sézary cell count. 4 The association of CTCL with increased class II HLA-DR5 and DQB*03 alleles suggests that the disease may arise in the setting of aberrant antigen stimulation or a genetic predisposition as seen with other autoimmune skin diseases. 5 Mutations in T cells may promote both T cell accumulation via defects in the Fas/Fas ligand death pathway 6 and attraction to the skin via mutations in skin-homing molecules.…”
Section: Cutaneous T-cell Lymphomamentioning
confidence: 99%